Test method for obtaining hydrogen concentration and stress of delayed cracking threshold of metal material

A method for evaluating hydrogen embrittlement in high-strength steel through sample preparation, electrochemical hydrogen charging, and stress loading addresses the lack of unified standards, enabling effective assessment of delayed cracking risk and improving safety.

CN119223743APending Publication Date: 2024-12-31BAOSHAN IRON & STEEL CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202310797111.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-30
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

There is no unified standard for hydrogen embrittlement evaluation of high-strength steel, and existing methods do not effectively assess the risk of delayed cracking under varying hydrogen concentrations and stress conditions, posing a significant risk to the safety and reliability of high-strength automotive steel.

Method used

A method involving sample preparation, electrochemical hydrogen charging, galvanizing, and stress loading to determine the threshold hydrogen concentration and stress for delayed cracking, using a four-point bending test to evaluate the risk of hydrogen embrittlement in high-strength steel.

Benefits of technology

Provides a standardized method to assess the risk of hydrogen embrittlement in high-strength steel, determining the threshold hydrogen concentration and stress for delayed cracking, thereby guiding preventive measures to enhance safety and reliability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119223743A_ABST
    Figure CN119223743A_ABST
Patent Text Reader

Abstract

The invention discloses a metal material delayed cracking threshold hydrogen concentration and stress test method, which comprises the following steps: S1, preparing a sample, treating the surface of the sample, and removing hydrogen concentration surface pollutants in the sample; s2, measuring the material tensile strength of the sample; s3, placing the sample in a hydrogen charging solution in an electrochemical constant current mode for charging hydrogen at different time lengths, and measuring the diffusible hydrogen content; s4, drawing a hydrogen concentration change curve, and preparing samples with different hydrogen concentrations from the samples in the step S3 according to the hydrogen concentration change curve; s5, galvanizing the sample prepared in the step S4 by adopting an electrogalvanizing process; and S6, stress loading is conducted on the sample galvanized in the step S5, and the threshold hydrogen concentration and the threshold stress value are obtained through standing and observation. The hydrogen resistance of the high-strength automobile steel is obtained, the hydrogen embrittlement cracking risk of the high-strength automobile steel under different hydrogen concentration and stress conditions is obtained, and prevention measures are provided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a hydrogen embrittlement risk assessment technology for metal materials, and more specifically to a method for obtaining a hydrogen concentration and stress test of a delayed cracking threshold of a metal material. Background Art

[0002] Hydrogen embrittlement is one of the important ways in which metal materials fail. It has the following significant characteristics: (1) deterioration of mechanical properties, especially significant reduction of elongation and cross-sectional shrinkage; (2) change of fracture mechanism, resulting in different fracture morphologies, which is mainly manifested in that as the hydrogen concentration in the material increases, the fracture mode changes from ductile dimple fracture to brittle cleavage or intergranular fracture; (3) fracture occurs suddenly without obvious signs, and thus often leads to serious consequences.

[0003] Hydrogen embrittlement may occur in metal materials during production, processing and use. Diffusible hydrogen is one of the key factors that cause hydrogen embrittlement of metals. The higher the concentration of diffusible hydrogen in the metal matrix, the greater the risk of hydrogen embrittlement of the metal material. In recent years, with the lightweight development of the automotive industry, high-strength automotive steel has been used more and more widely, the strength of high-strength steel has become higher and higher, and the risk of hydrogen embrittlement has also become higher and higher. Diffusible hydrogen is the core factor that causes hydrogen embrittlement in high-strength steel. Hydrogen is inevitably introduced into high-strength steel during the production stages such as smelting, pickling, electroplating, welding, and subsequent processing and use by users. Hydrogen exists in steel in two states, one in the form of non-diffusible hydrogen and the other in the form of diffusible hydrogen. Diffusible hydrogen can diffuse in steel and be enriched in defects, grain boundaries, etc. The interaction between diffusible hydrogen and stress is the main reason for hydrogen embrittlement and delayed fracture of ultra-high-strength steel.

[0004] At present, there is no unified standard for the hydrogen embrittlement evaluation test of high-strength steel in China. The standards adopted by major domestic OEMs include Mazda's "HYDROGEN EMBRITTLEMENT EVAL." material testing standard, which mainly evaluates high-strength steel plates and high-strength steel welding parts. After electrodeposition of U-shaped and V-shaped specimens, observe whether cracks occur, and then test the diffusible hydrogen content of the specimens by TDA method. General Motors' "SEP 1970 Hydrogen Cracking Test" standard, which mainly processes the specimen into a U-shaped specimen and places it for 720 hours, and then observes whether cracks occur. At the same time, a perforated tensile specimen is made for stretching, and the tensile force is the yield strength. After 96 hours of stretching, observe whether the specimen breaks. Tesla's "TM-2011 Rev 06 Steel, Rolled Product-Sheet and Strip" standard requires that according to Tesla's material requirements, high-strength steel needs to pass a 300-hour hydrochloric acid immersion test. Nissan's "HCl Test Procedure for U-bend test samples for Nissan Approval" standard mainly applies loads of different stress levels to high-strength steel and then immerses it in hydrochloric acid solution for 300-1000 hours to observe whether there are cracks on the surface of the high-strength steel. Summary of the invention

[0005] In view of the defects existing in the prior art, the purpose of the present invention is to provide a method for obtaining the hydrogen concentration and stress test threshold for delayed cracking of metal materials, to obtain the hydrogen resistance of high-strength automotive steel, to obtain the risk of hydrogen embrittlement cracking of high-strength automotive steel under different hydrogen concentrations and stress conditions, and to provide preventive measures for hydrogen embrittlement of high-strength steel.

[0006] To achieve the above object, the present invention adopts the following technical solution:

[0007] A method for obtaining a delayed cracking threshold hydrogen concentration and stress test of a metal material comprises the following steps:

[0008] S1. Prepare a sample and treat the surface of the sample to remove surface contaminants that affect the hydrogen concentration in the sample;

[0009] S2, measuring the material tensile strength of the sample;

[0010] S3, placing the sample in a hydrogen charging solution for different lengths of time using an electrochemical constant current mode, and then measuring the diffusible hydrogen content;

[0011] S4, drawing a hydrogen concentration change curve according to the hydrogen concentration measured in S3, and repeating the sample in step S3 to prepare samples with different hydrogen concentrations according to the hydrogen concentration change curve;

[0012] S5, galvanizing the sample prepared in step S4 by using an electrogalvanizing process;

[0013] S6. Stress loading is performed on the sample after galvanizing in step S5, and the sample is placed for observation to obtain a threshold hydrogen concentration and a threshold stress value.

[0014] Preferably, the size of the sample in step S1 is 120 mm*20 mm, and the number is 30 pieces;

[0015] The surface of the sample is treated by an acetone ultrasonic method;

[0016] Using a heating furnace to remove the hydrogen concentration in the sample;

[0017] Preferably, the acetone ultrasonic method is performed for 15 minutes;

[0018] The heating temperature of the heating furnace is 150° C. to 200° C., and the heating time is 15 min to 2 h, so that the hydrogen concentration in the sample is reduced to below 0.02 ppm;

[0019] The thermal desorption method heats the sample to 400° C., and the hydrogen release time is 10 min to 1 h.

[0020] Preferably, in step S2, three samples are taken and subjected to a slow tensile test using a slow tensile testing machine to obtain a slow tensile curve, and the tensile strength of the three samples is determined from the slow tensile curve.

[0021] Preferably, the average value of the tensile strength of the three samples is taken as the tensile strength of this slow tensile test.

[0022] Preferably, in step S3,

[0023] A hydrogen analyzer is used to heat the sample to release hydrogen by thermal desorption method to measure the diffusible hydrogen content;

[0024] The current in the electrochemical constant current mode was 10 mA / cm 2 , the hydrogen filling time is 10min~10h;

[0025] The hydrogen charging solution is 0.5 mol / L H2SO4+0.3 g / L thiourea solution.

[0026] Preferably, drawing the hydrogen concentration variation curve in step S4 specifically includes:

[0027] After hydrogenation, the samples are measured one by one according to the hydrogenation time until the difference in hydrogen content is less than 0.1 ppm. At this time, the hydrogen content is the saturated hydrogen concentration Cm of the sample. At the same time, the relationship between the hydrogenation concentration and time is recorded to establish the hydrogen concentration change curve;

[0028] The hydrogen concentration variation curve is then used to prepare the sample having a hydrogen concentration of 0.05 to 0.8 times.

[0029] Preferably, the electrogalvanizing process in step S5 specifically includes:

[0030] Use alkaline zinc plating solution, the formula is sodium hydroxide: 100g / L~120g / L, zinc oxide: 8g / L~12g / L, triethanolamine: 20ml / L~30ml / L, temperature is 10℃~40℃, current density is 5mA / cm 2 ~20mA / cm 2 ;

[0031] The electroplating time is 5 min to 30 min, and the coating thickness is 5 μm to 12 μm.

[0032] Preferably, the stress loading in step S6 specifically includes:

[0033] A four-point bending test method is used to perform stress loading using a top screw. Before loading, a strain test gauge is installed so that the top of the strain test gauge is aligned with the center point of the sample after galvanizing. The strain required for different stresses is calculated according to formula (1);

[0034]

[0035] Wherein, E represents Young's elastic modulus 209GPa; t represents the thickness of the test sample; y represents the bending deflection of the sample; H represents the distance between the outer loading point; A represents the distance between the outer loading point and the inner loading point in the X direction; and h represents the distance between the inner loading point.

[0036] Preferably, according to the hydrogen concentration of the sample after galvanizing, 0.1 to 1.0 times of TS stress is applied to the sample, and then the loaded sample is placed in air for observation for 300 hours.

[0037] Preferably, the threshold hydrogen concentration C is determined HIC Specifically include:

[0038] Observe the cracking of the samples under different hydrogen concentrations under the same stress conditions and record Cy and Cn. HIC =(Cy+Cn) / 2, and the threshold hydrogen concentration C is obtained. HIC ;

[0039] Cy represents the minimum hydrogen concentration at which hydrogen-induced delayed fracture can occur within a specified time; Cn represents the maximum hydrogen concentration at which hydrogen-induced delayed fracture does not occur within a specified time;

[0040] Determine the threshold stress value σ HIC Specifically include:

[0041] Observe the cracking of the samples under different hydrogen concentrations under the same stress conditions and record σy and σn. HIC =(σy+σn) / 2, and the threshold hydrogen concentration σ is obtained. HIC ;

[0042] σy represents the minimum stress at which hydrogen-induced delayed fracture can occur within a specified time; σn represents the maximum stress at which hydrogen-induced delayed fracture does not occur within a specified time.

[0043] The present invention provides a method for obtaining a delayed cracking threshold hydrogen concentration and stress test for metal materials, which can not only obtain the delayed cracking threshold hydrogen concentration of high-strength steel, but also combine stress with hydrogen concentration to obtain the minimum stress value of delayed cracking under different hydrogen concentrations. The threshold hydrogen concentration obtained by the present invention can provide a reference for the delayed cracking risk of high-strength steel and provide guidance for the improvement of hydrogen resistance and safe use of high-strength steel. BRIEF DESCRIPTION OF THE DRAWINGS

[0044] Figure 1 It is a schematic flow chart of a method for obtaining a delayed cracking threshold hydrogen concentration and stress test of a metal material according to the present invention;

[0045] Figure 2 It is a schematic diagram of obtaining the delayed cracking threshold hydrogen concentration of metal materials and stress loading in the stress test method of the present invention. DETAILED DESCRIPTION

[0046] In order to better understand the above technical solution of the present invention, the technical solution of the present invention is further described below in conjunction with the accompanying drawings and embodiments.

[0047] Combination Figure 1 As shown, the present invention provides a method for obtaining a delayed cracking threshold hydrogen concentration and stress test of a metal material, comprising the following steps:

[0048] S1. Prepare the sample and treat the surface of the sample to remove the hydrogen concentration in the sample, and then measure the diffusible hydrogen content, specifically including:

[0049] The sample size was cut into 120mm*20mm by shearing method, ensuring that the surface of the sample was flat and without bending. The number of each sample was 30 pieces;

[0050] The sample was ultrasonicated for 15 min using acetone ultrasonic method to ensure the surface of the sample was clean;

[0051] The sample is heated in a heating furnace at 150°C to 200°C for 15 minutes to 2 hours to reduce the hydrogen concentration in the sample to below 0.02 ppm;

[0052] The sample was heated at 400°C to release hydrogen by thermal desorption method using a hydrogen analyzer from Bruker, Germany, for 10 min to 1 h, and the diffusible hydrogen content was measured.

[0053] S2. Measure the material tensile strength (TS) of the sample, including:

[0054] Using a slow tensile testing machine, 3 samples were selected for slow tensile testing to obtain a slow tensile curve. The tensile strength of the 3 samples was determined from the curve. To ensure data accuracy, the difference in the tensile strength of the 3 samples must be less than 100 MPa. The average tensile strength of the 3 samples was taken as the tensile strength of the test material.

[0055] S3, using electrochemical constant current mode with 10mA / cm 2 The samples after dehydrogenation treatment were placed in hydrogen charging solution for different lengths of hydrogen charging using a current of 10 minutes to 10 hours.

[0056] The sample is placed in a hydrogen-filled solution and stored for later use;

[0057] The hydrogen charging solution is 0.5 mol / L H2SO4 + 0.3 g / L thiourea solution, and is stored at room temperature for 24 hours for use.

[0058] S4, drawing a hydrogen concentration change curve, and preparing samples with different hydrogen concentrations from the samples in step S3 according to the hydrogen concentration change curve, specifically including:

[0059] The samples after hydrogenation are measured one by one according to the hydrogenation time until the difference in hydrogen content is less than 0.1ppm. At this time, the hydrogen content is the saturated hydrogen concentration Cm of the sample. At the same time, the relationship between the hydrogenation concentration and time is recorded to establish a hydrogen concentration change curve;

[0060] The hydrogen concentration variation curve is then used to prepare hydrogen concentration samples with hydrogen concentrations ranging from 0.05 times to 0.8 times, followed by immediate galvanizing.

[0061] S5, zinc-plating the sample prepared in step S4 by using an electro-galvanizing process, wherein the electro-galvanizing process specifically comprises:

[0062] Use alkaline zinc plating solution, the formula is sodium hydroxide: 100g / L~120g / L, zinc oxide: 8g / L~12g / L, triethanolamine: 20ml / L~30ml / L, temperature is 10℃~40℃, current density is 5mA / cm 2 ~20mA / cm 2 ;

[0063] The electroplating time is 5min to 30min, ensuring that all surfaces of the material are galvanized, and the coating is uniform without missing plating, and the coating thickness is 5μm to 12μm.

[0064] S6, stress loading is performed on the sample after galvanizing in step S5, and the threshold hydrogen concentration and threshold stress value are obtained by observation. The stress loading specifically includes:

[0065] Combination Figure 2 As shown, a four-point bending test method is used, and stress loading is performed using a top screw. Before loading, a strain test table is installed so that the top of the strain test table is aligned with the center point of the galvanized sample. The strain required for different stresses is calculated according to formula (1);

[0066]

[0067] Wherein, E represents Young's elastic modulus 209GPa; t represents the thickness of the test sample; y represents the bending deflection of the sample; H represents the distance between the outer loading point; A represents the distance between the outer loading point and the inner loading point in the X direction; and h represents the distance between the inner loading point.

[0068] By stress loading, 0.1 to 1.0 times of TS stress was applied to the samples according to the hydrogen concentration of the samples after galvanizing. The different samples and hydrogen concentration combinations are shown in Table 1. The loaded samples were then placed in the air for observation for 300 hours.

[0069] Table 1 Hydrogen concentration and stress combination of different samples

[0070] 0.ITS 0.3TS 0.5TS 0.8TS 1.0TS 0.05Cm Sample 1 Sample 2 Sample 3 Sample 4 Sample 5 0.1Cm Sample 6 Sample 7 Sample 8 Sample 9 Sample 10 0.3Cm Sample 11 Sample 12 Sample 13 Sample 14 Sample 15 0.5Cm Sample 16 Sample 17 Sample 18 Sample 19 Sample 20 0.8Cm Sample 21 Sample 22 Sample 23 Sample 24 Sample 25

[0071] Determination of threshold hydrogen concentration C HIC Specifically include:

[0072] Observe the cracking of samples with different hydrogen concentrations under the same stress conditions and record Cy and Cn. HIC =(Cy+Cn) / 2, and the threshold hydrogen concentration C is obtained. HIC ;

[0073] Cy represents the minimum hydrogen concentration at which hydrogen-induced delayed fracture can occur within a specified time (i.e., the fracture cut-off time); Cn represents the maximum hydrogen concentration at which hydrogen-induced delayed fracture does not occur within a specified time;

[0074] Determination of threshold stress value σ HIC Specifically include:

[0075] Observe the cracking of samples with different hydrogen concentrations under the same stress conditions and record σy and σn. HIC =(σy+σn) / 2, and the threshold hydrogen concentration σ is obtainedHIC ;

[0076] σy represents the minimum stress at which hydrogen-induced delayed fracture can occur within a specified time (i.e., the fracture cut-off time); σn represents the maximum stress at which hydrogen-induced delayed fracture does not occur within a specified time.

[0077] The principle of the present invention is that hydrogen embrittlement is mainly related to the material itself, the hydrogen concentration in the material matrix and the stress. Therefore, for each type of high-strength steel, since its organizational composition has been determined, its risk of hydrogen embrittlement and delayed cracking is mainly related to the hydrogen concentration in the matrix and the stress it bears. The diffusion rate of diffusible hydrogen in the zinc layer is much lower than the diffusion rate of hydrogen in the steel. Electrochemical hydrogenation is used to obtain steel samples with different hydrogen concentrations, and the samples are covered with a galvanized layer to achieve the effect of sealing hydrogen in the sample. Subsequently, different stresses are applied to the samples containing different hydrogen concentrations and galvanized to obtain the delayed cracking of steel under different hydrogen concentrations and stress conditions. At present, the standards of major OEMs have determined that if there is no cracking after immersion in hydrochloric acid solution for 300 hours, it can be considered that there is no risk of hydrogen embrittlement and delayed cracking. Therefore, in the experiment, 300 hours is limited. The highest stress and hydrogen concentration during which no cracking occurs can be used as the threshold stress and hydrogen concentration of the high-strength steel.

[0078] The present invention mainly studies high-strength automobile steel, and is also applicable to other high-strength metal materials. The bare high-strength steel plate can be directly used in this method, and the high-strength steel or metal material with coating on the surface needs to use a suitable method to remove the surface coating without changing the material structure before using the method of the present invention.

[0079] Example 1

[0080] DP980 cold-rolled finished plate was selected from the production site as the test material. The specific steps are as follows:

[0081] S1. Sample preparation: Cut the sample into a size of 120mm*20mm by shearing method, ensuring that the sample surface is flat and without bending, 30 pieces of each sample;

[0082] S2. Sample surface treatment: Use acetone ultrasonic method to ultrasonicate the sample for 15 minutes to ensure that the sample surface is clean;

[0083] S3. Remove hydrogen from the sample: Use a heating furnace to heat the high-strength steel at 150°C for 20 minutes to reduce the hydrogen concentration to below 0.02ppm;

[0084] S4. Hydrogen measurement method: Using a German Bruker hydrogen analyzer, the sample was heated at 400°C to release hydrogen for 25 minutes using the thermal desorption method to obtain the diffusible hydrogen content;

[0085] S5. Tensile strength (TS) measurement: Use a slow tensile testing machine to select 3 samples for slow tensile testing to obtain a slow tensile curve. Determine the tensile strength of the 3 samples from the curve. To ensure data accuracy, the difference in the tensile strength of the 3 samples must be less than 100Mpa. The average tensile strength of the 3 samples is taken as the tensile strength of the test material.

[0086] S6. Prepare hydrogen charging solution: prepare 0.5 mol / L H2SO4 + 0.3 g / L thiourea solution as hydrogen charging solution, and store it at room temperature for 24 hours for use;

[0087] S7, electrochemical hydrogen charging: using electrochemical constant current mode with 10mA / cm 2 The samples after dehydrogenation treatment were placed in hydrogen charging solution for different lengths of hydrogen charging current, ranging from 10 minutes to 10 hours.

[0088] S8. Sample preservation: the hydrogen-filled samples are placed in liquid nitrogen for future use;

[0089] S9, hydrogen concentration change curve drawing: hydrogen-filled samples are measured one by one according to the hydrogen filling time, until the difference between the hydrogen contents is less than 0.1ppm, and the saturated hydrogen concentration Cm of the sample is obtained to be 2ppm, and the relationship between the hydrogen filling concentration and time is recorded at the same time, and a hydrogen concentration change curve is established;

[0090] S10, electrogalvanizing process: In order to avoid the reaction between the material and the acidic solution to cause hydrogen absorption, the present invention adopts an alkaline zinc plating solution with a formula of 100g / L sodium hydroxide, 10g / L zinc oxide, 20ml / L triethanolamine, a temperature of 26°C, and a current density of 10mA / cm 2 ;

[0091] S11. Preparation of samples with different hydrogen concentrations: using the hydrogen concentration curve to prepare samples with hydrogen concentrations of 0.05 to 0.8 times Cm, followed by immediate galvanizing;

[0092] S12, sample galvanizing: galvanize the sample in step 11 by using the electrogalvanizing process, the galvanizing time is 10 minutes, ensure that all surfaces of the material are galvanized, and the coating is uniform without missing coating, and the coating thickness is 6um;

[0093] S13. Stress loading method: The stress loading method uses the four-point bending test method. This method uses the top screw to load the stress. Before loading the sample, the strain test table is installed to ensure that the top of the stress test table is aligned with the center point of the sample. The strain required for different stresses is calculated according to formula (2) to ensure the accuracy of the loading stress.

[0094]

[0095] S14. Stress loading of hydrogen-filled samples: Using the stress loading method in step 13, apply 0.1 to 1.0 times TS stress to samples with different hydrogen concentrations after galvanizing. The different samples and hydrogen concentration combinations are shown in Table 2 below. The loaded samples are then placed in the air for observation for 300 hours.

[0096] Table 2 Hydrogen concentration and stress combination of different samples

[0097] 0.1TS 0.3TS 0.5TS 0.8TS 1.0TS 0.05Cm Sample 1 Sample 2 Sample 3 Sample 4 Sample 5 0.1Cm Sample 6 Sample 7 Sample 8 Sample 9 Sample 10 0.3Cm Sample 11 Sample 12 Sample 13 Sample 14 Sample 15 0.5Cm Sample 16 Sample 17 Sample 18 Sample 19 Sample 20 0.8Cm Sample 21 Sample 22 Sample 23 Sample 24 Sample 25

[0098] S15, threshold hydrogen concentration (C HIC ) Determination: Observe the cracking of samples with different hydrogen concentrations under the same stress conditions and record Cy and Cn. Cy is the minimum hydrogen concentration that can cause hydrogen-induced delayed fracture within a specified time (i.e., the fracture cut-off time), and Cn is the maximum hydrogen concentration that does not cause hydrogen-induced delayed fracture within a specified time. Use the formula C HIC =(Cy+Cn) / 2, we can get the threshold hydrogen concentration C HIC .

[0099] S16, threshold stress value (σ HIC ) determination: observe the cracking of samples with different stresses under the same hydrogen concentration and record σy and σn. σy is the minimum stress that can cause hydrogen-induced delayed fracture within a specified time (i.e., the fracture cut-off time), and σn is the maximum stress that does not cause hydrogen-induced delayed fracture within a specified time. Use the formula σ HIC =(σy+σn) / 2 to obtain the threshold stress value.

[0100] Steel Type Cy / ppm Cn / ppm σy / Mpa σn / Mpa <![CDATA[C HIC / ppm]]> <![CDATA[σ HIC ]]> DP980 0.1 0.2 820 1006 0.15 913

[0101] Example 2

[0102] DP780 cold-rolled finished plate was selected from the production site as the test material. The specific steps are as follows:

[0103] S1. Sample preparation: Cut the sample into a size of 120mm*20mm by shearing method, ensuring that the sample surface is flat and without bending, 30 pieces of each sample;

[0104] S2. Sample surface treatment: Use acetone ultrasonic method to ultrasonicate the sample for 15 minutes to ensure that the sample surface is clean;

[0105] S3. Remove hydrogen from the sample: Use a heating furnace to heat the high-strength steel at 150°C for 18 minutes to reduce the hydrogen concentration to below 0.02ppm;

[0106] S4. Hydrogen measurement method: Using a German Bruker hydrogen analyzer, the sample was heated at 400°C to release hydrogen for 30 minutes using the thermal desorption method to obtain the diffusible hydrogen content;

[0107] S5. Tensile strength (TS) measurement: Use a slow tensile testing machine to select 3 samples for slow tensile testing to obtain a slow tensile curve. Determine the tensile strength of the 3 samples from the curve. To ensure data accuracy, the difference in the tensile strength of the 3 samples must be less than 100Mpa. The average tensile strength of the 3 samples is taken as the tensile strength of the test material.

[0108] S6. Prepare hydrogen charging solution: prepare 0.5 mol / L H2SO4 + 0.3 g / L thiourea solution as hydrogen charging solution, and store it at room temperature for 24 hours for use;

[0109] S7, electrochemical hydrogen charging: using electrochemical constant current mode with 10mA / cm 2 The samples after dehydrogenation treatment were placed in hydrogen charging solution for different lengths of hydrogen charging current, ranging from 10 minutes to 10 hours.

[0110] S8. Sample preservation: the hydrogen-filled samples are placed in liquid nitrogen for future use;

[0111] S9, hydrogen concentration change curve drawing: hydrogen-filled samples are measured one by one according to the hydrogen filling time, until the difference between the hydrogen contents is less than 0.1ppm, and the saturated hydrogen concentration Cm of the sample is obtained to be 2.4ppm. At the same time, the relationship between the hydrogen filling concentration and time is recorded to establish a hydrogen concentration change curve;

[0112] S10, electrogalvanizing process: In order to avoid the reaction between the material and the acidic solution to cause hydrogen absorption, the present invention adopts an alkaline zinc plating solution with a formula of 100g / L sodium hydroxide, 10g / L zinc oxide, 20ml / L triethanolamine, a temperature of 26°C, and a current density of 10mA / cm 2 ;

[0113] S11. Preparation of samples with different hydrogen concentrations: using the hydrogen concentration curve to prepare samples with hydrogen concentrations of 0.05 to 0.8 times Cm, followed by immediate galvanizing;

[0114] S12, sample galvanizing: galvanize the sample in step 11 by using the electrogalvanizing process, the galvanizing time is 10 minutes, ensure that all surfaces of the material are galvanized, and the coating is uniform without missing coating, and the coating thickness is 6um;

[0115] S13. Stress loading method: The stress loading method uses the four-point bending test method. This method uses the top screw to load the stress. Before loading the sample, the strain test table is installed to ensure that the top of the stress test table is aligned with the center point of the sample. The strain required for different stresses is calculated according to formula (3) to ensure the accuracy of the loading stress.

[0116]

[0117] S14. Stress loading of hydrogen-filled samples: Using the stress loading method in step 13, apply 0.1 to 1.0 times TS stress to samples with different hydrogen concentrations after galvanizing. The different samples and hydrogen concentration combinations are shown in Table 3 below. The loaded samples are then placed in the air for observation for 300 hours.

[0118] 0.1TS 0.3TS 0.5TS 0.8TS 1.0TS 0.05Cm Sample 1 Sample 2 Sample 3 Sample 4 Sample 5 0.1Cm Sample 6 Sample 7 Sample 8 Sample 9 Sample 10 0.3Cm Sample 11 Sample 12 Sample 13 Sample 14 Sample 15 0.5Cm Sample 16 Sample 17 Sample 18 Sample 19 Sample 20 0.8Cm Sample 21 Sample 22 Sample 23 Sample 24 Sample 25

[0119] S15, threshold hydrogen concentration (C HIC ) Determination: Observe the cracking of samples with different hydrogen concentrations under the same stress conditions and record Cy and Cn. Cy is the minimum hydrogen concentration that can cause hydrogen-induced delayed fracture within a specified time (i.e., the fracture cut-off time), and Cn is the maximum hydrogen concentration that does not cause hydrogen-induced delayed fracture within a specified time. Use the formula C HIC =(Cy+Cn) / 2, we can get the threshold hydrogen concentration C HIC .

[0120] S16, threshold stress value (σ HIC ) determination: observe the cracking of samples with different stresses under the same hydrogen concentration and record σy and σn. σy is the minimum stress that can cause hydrogen-induced delayed fracture within a specified time (i.e., the fracture cut-off time), and σn is the maximum stress that does not cause hydrogen-induced delayed fracture within a specified time. Use the formula σ HIC =(σy+σn) / 2 to obtain the threshold stress value.

[0121] Steel Type Cy / ppm Cn / ppm σy / Mpa σn / Mpa <![CDATA[C HIC / ppm]]> <![CDATA[σ HIC ]]> DP980 0.12 0.24 644 792 0.18 718

[0122] Example 3

[0123] Select MS1180 cold-rolled finished plate from the production site as the test material, and the specific steps are as follows:

[0124] S1. Sample preparation: Cut the sample into a size of 120mm*20mm by shearing method, ensuring that the sample surface is flat and without bending, 30 pieces of each sample;

[0125] S2. Sample surface treatment: Use acetone ultrasonic method to ultrasonicate the sample for 15 minutes to ensure that the sample surface is clean;

[0126] S3. Remove hydrogen from the sample: Use a heating furnace to heat the high-strength steel at 170°C for 20 minutes to reduce the hydrogen concentration to below 0.02ppm;

[0127] S4. Hydrogen measurement method: Using a German Bruker hydrogen analyzer, the sample was heated at 400°C to release hydrogen for 25 minutes using the thermal desorption method to obtain the diffusible hydrogen content;

[0128] S5. Tensile strength (TS) measurement: Use a slow tensile testing machine to select 3 samples for slow tensile testing to obtain a slow tensile curve. Determine the tensile strength of the 3 samples from the curve. To ensure data accuracy, the difference in the tensile strength of the 3 samples must be less than 100Mpa. The average tensile strength of the 3 samples is taken as the tensile strength of the test material.

[0129] S6. Prepare hydrogen charging solution: prepare 0.5 mol / L H2SO4 + 0.3 g / L thiourea solution as hydrogen charging solution, and store it at room temperature for 24 hours for use;

[0130] S7, electrochemical hydrogen charging: using electrochemical constant current mode with 10mA / cm 2 The samples after dehydrogenation treatment were placed in hydrogen charging solution for different lengths of hydrogen charging current, ranging from 10 minutes to 10 hours.

[0131] S8. Sample preservation: the hydrogen-filled samples are placed in liquid nitrogen for future use;

[0132] S9, hydrogen concentration change curve drawing: hydrogen-filled samples are measured one by one according to the hydrogen filling time, until the difference between the hydrogen contents is less than 0.1ppm, and the saturated hydrogen concentration Cm of the sample is obtained to be 1.5ppm. At the same time, the relationship between the hydrogen filling concentration and time is recorded to establish a hydrogen concentration change curve;

[0133] S10, electrogalvanizing process: In order to avoid the reaction between the material and the acidic solution to cause hydrogen absorption, the present invention adopts an alkaline zinc plating solution with a formula of 100g / L sodium hydroxide, 10g / L zinc oxide, 20ml / L triethanolamine, a temperature of 26°C, and a current density of 10mA / cm 2 ;

[0134] S11. Preparation of samples with different hydrogen concentrations: using the hydrogen concentration curve to prepare samples with hydrogen concentrations of 0.05 to 0.8 times Cm, followed by immediate galvanizing;

[0135] S12, sample galvanizing: galvanize the sample in step 11 by using the electrogalvanizing process, the galvanizing time is 8 minutes, ensure that all surfaces of the material are galvanized, and the coating is uniform without missing coating, and the coating thickness is 5um;

[0136] S13. Stress loading method: The stress loading method uses the four-point bending test method. This method uses the top screw to load the stress. Before loading the sample, the strain test table is installed to ensure that the top of the stress test table is aligned with the center point of the sample. The strain required for different stresses is calculated according to formula (4) to ensure the accuracy of the loading stress.

[0137]

[0138] S14. Stress loading of hydrogen-filled samples: Using the stress loading method in step 13, apply 0.1 to 1.0 times TS stress to samples with different hydrogen concentrations after galvanizing. The different samples and hydrogen concentration combinations are shown in Table 4 below. The loaded samples are then placed in the air for observation for 300 hours.

[0139] Table 4 Hydrogen concentration and stress combination of different samples

[0140] 0.1TS 0.3TS 0.5TS 0.8TS 1.0TS 0.05Cm Sample 1 Sample 2 Sample 3 Sample 4 Sample 5 0.1Cm Sample 6 Sample 7 Sample 8 Sample 9 Sample 10 0.3Cm Sample 11 Sample 12 Sample 13 Sample 14 Sample 15 0.5Cm Sample 16 Sample 17 Sample 18 Sample 19 Sample 20 0.8Cm Sample 21 Sample 22 Sample 23 Sample 24 Sample 25

[0141] S15, threshold hydrogen concentration (C HIC ) Determination: Observe the cracking of samples with different hydrogen concentrations under the same stress conditions and record Cy and Cn. Cy is the minimum hydrogen concentration that can cause hydrogen-induced delayed fracture within a specified time (i.e., the fracture cut-off time), and Cn is the maximum hydrogen concentration that does not cause hydrogen-induced delayed fracture within a specified time. Use the formula C HIC =(Cy+Cn) / 2, we can get the threshold hydrogen concentration C HIC .

[0142] S16, threshold stress value (o HIC ) determination: observe the cracking of samples with different stresses under the same hydrogen concentration and record σy and σn. σy is the minimum stress that can cause hydrogen-induced delayed fracture within a specified time (i.e., the fracture cut-off time), and σn is the maximum stress that does not cause hydrogen-induced delayed fracture within a specified time. Use the formula σ HIC =(σy+σn) / 2 to obtain the threshold stress value.

[0143] Steel Type Cy / ppm Cn / ppm σy / Mpa σn / Mpa <![CDATA[C HIC / ppm]]> <![CDATA[σ HIC ]]> DP980 0.08 0.15 968 1195 0.12 1081

[0144] Those skilled in the art should recognize that the above embodiments are only used to illustrate the present invention, and are not intended to limit the present invention. As long as they are within the spirit of the present invention, any changes or modifications to the above embodiments will fall within the scope of the claims of the present invention.

Claims

1. A method for obtaining a hydrogen concentration and stress test for a metal material delayed cracking threshold, characterized in that: The following steps are involved: S1. Prepare a sample and treat the surface of the sample to remove surface contaminants with hydrogen concentration in the sample; S2, measuring the material tensile strength of the sample; S3, placing the sample in a hydrogen charging solution for different lengths of time using an electrochemical constant current mode, and then measuring the diffusible hydrogen content; S4, drawing a hydrogen concentration change curve according to the hydrogen concentration measured in S3, and repeating the sample in step S3 to prepare samples with different hydrogen concentrations according to the hydrogen concentration change curve; S5, galvanizing the sample prepared in step S4 by using an electrogalvanizing process; S6. Stress loading is performed on the sample after galvanizing in step S5, and the sample is placed for observation to obtain a threshold hydrogen concentration and a threshold stress value.

2. The method for obtaining the delayed cracking threshold hydrogen concentration and stress test of metal materials according to claim 1, characterized in that: The size of the sample in step S1 is 120 mm*20 mm, and the number is 30 pieces; The surface of the sample is treated by an acetone ultrasonic method; The hydrogen concentration in the sample is removed by heating in a heating furnace.

3. The method for obtaining the delayed cracking threshold hydrogen concentration and stress test of metal materials according to claim 2, characterized in that: The time of the acetone ultrasonic method is 15 minutes; The heating temperature of the heating furnace is 150° C. to 200° C., and the heating time is 15 min to 2 h, so that the hydrogen concentration in the sample is reduced to below 0.02 ppm; The thermal desorption method heats the sample to 400° C., and the hydrogen release time is 10 min to 1 h.

4. The method for obtaining the delayed cracking threshold hydrogen concentration and stress test of metal materials according to claim 2, characterized in that: In the step S2, three samples are taken and subjected to a slow tensile test using a slow tensile testing machine to obtain a slow tensile curve, and the tensile strength of the three samples is determined from the slow tensile curve.

5. The method for obtaining the delayed cracking threshold hydrogen concentration and stress test of metal materials according to claim 4, characterized in that: The average value of the tensile strength of the three samples is taken as the tensile strength of this slow tensile test.

6. The method for obtaining the delayed cracking threshold hydrogen concentration and stress test of metal materials according to claim 4, characterized in that: In the step S3, A hydrogen analyzer is used to heat the sample to release hydrogen by thermal desorption method to measure the diffusible hydrogen content; The current in the electrochemical constant current mode was 10 mA / cm 2 , the hydrogen filling time is 10min~10h; The hydrogen charging solution is 0.5 mol / L H2SO4+0.3 g / L thiourea solution.

7. The method for obtaining the delayed cracking threshold hydrogen concentration and stress test of metal materials according to claim 6, characterized in that: Drawing the hydrogen concentration variation curve in step S4 specifically includes: After hydrogenation, the samples are measured one by one according to the hydrogenation time until the difference in hydrogen content is less than 0.1 ppm. At this time, the hydrogen content is the saturated hydrogen concentration Cm of the sample. At the same time, the relationship between the hydrogenation concentration and time is recorded to establish the hydrogen concentration change curve; The hydrogen concentration variation curve is then used to prepare the sample having a hydrogen concentration of 0.05 to 0.8 times.

8. The method for obtaining the delayed cracking threshold hydrogen concentration and stress test of metal materials according to claim 7, characterized in that: The electrogalvanizing process in step S5 specifically includes: Use alkaline zinc plating solution, the formula is sodium hydroxide: 100g / L~120g / L, zinc oxide: 8g / L~12g / L, triethanolamine: 20ml / L~30ml / L, temperature is 10℃~40℃, current density is 5mA / cm 2 ~20mA / cm 2 ; The electroplating time is 5 min to 30 min, and the coating thickness is 5 μm to 12 μm.

9. The method for obtaining the delayed cracking threshold hydrogen concentration and stress test of metal materials according to claim 8, characterized in that: The stress loading in step S6 specifically includes: A four-point bending test method is used to perform stress loading using a top screw. Before loading, a strain test gauge is installed so that the top of the strain test gauge is aligned with the center point of the sample after galvanizing. The strain required for different stresses is calculated according to formula (1); Wherein, E represents Young's elastic modulus 209GPa; t represents the thickness of the test sample; y represents the bending deflection of the sample; H represents the distance between the outer loading point; A represents the distance between the outer loading point and the inner loading point in the X direction; h represents the distance between the inner loading point.

10. The method for obtaining the delayed cracking threshold hydrogen concentration and stress test of metal materials according to claim 9, characterized in that: According to the hydrogen concentration of the sample after galvanizing, 0.1 to 1.0 times of TS stress were applied to the sample, and then the loaded sample was placed in the air for observation for 300 hours.

11. The method for obtaining the delayed cracking threshold hydrogen concentration and stress test of metal materials according to claim 10, characterized in that: Determine the threshold hydrogen concentration C HIC Specifically include: Observe the cracking of the samples under different hydrogen concentrations under the same stress conditions and record Cy and Cn. HIC =(Cy+Cn) / 2, and the threshold hydrogen concentration C is obtained. HIC ; Cy represents the minimum hydrogen concentration at which hydrogen-induced delayed fracture can occur within a specified time; Cn represents the maximum hydrogen concentration at which hydrogen-induced delayed fracture does not occur within a specified time; Determine the threshold stress value σ HIC Specifically include: Observe the cracking of the samples under different hydrogen concentrations under the same stress conditions and record σy and σn. HIC =(σy+σn) / 2, and the threshold hydrogen concentration σ is obtained. HIC ; σy represents the minimum stress at which hydrogen-induced delayed fracture can occur within a specified time; σn represents the maximum stress at which hydrogen-induced delayed fracture does not occur within a specified time.

Citation Information

Cited By

  • Method for testing fracture limit hydrogen content of high-strength steel material for automobile based on stress attenuation

    CN121612690A